எங்கள் ஆசிரியர்களுடன் 1-ஆன்-1 ஆலோசனை நேரத்தைப் பெறுங்கள். டாப்பர் ஆவதற்கு நாங்கள் பயிற்சி அளிப்போம்

Book Free Demo
Identity –\(3\): (ab)2=a22ab+b2
If we replace the variable \((-b)\) in the identity -\((2)\) instead of \((b)\), we get a new identity, that is(ab)2=a22ab+b2.
Let us see how we got it.
We know the identity –\((2)\), that is (a+b)2=a2+2ab+b2. Substitute the variable \((-b)\) in the identity \((2)\) instead of \((b)\).
Then, we get:
From the above equation, we can observe that when we change the sign of \(b\), the second term \(2ab\) alone is changed, the other term remains unchanged.
Now we see an example to understand this concept better.
Simplify the expression (4x11y)2 using the appropriate identity.
We can simplify the given expression (4x11y)2, using the identity (ab)2=a22ab+b2.
Here, \(a =4x\); \(b = 11y\)
Now, substitute \(a\), and \(b\) values in the identity.
Therefore, (4x11y)2 \(=\) 16x288xy+121y2.